“O corpo entre a rede, o anzol e o rio”: sentidos e significados da prática da pesca em Tocantinópolis - TO - Nascimento, Mateus Filho Vieira do (Universidade Federal do Tocantins, 2023)
This work aims to understand the senses and meanings of fishing, as a body and leisure practice, for the riverside community in the city of Tocantinópolis / TO. Fishing, in addition to subsistence and economic activity in the region, makes use of body techniques covered with social meanings, which reveal important perspectives about the observed daily life, which directly imply in the education of the subjects' bodies. Understanding that Physical Education, as a field of knowledge, needs to potentialize the various forms of use and appropriation of the body, especially in its sociocultural and educational sense, the practice of fishing can be an important content in the vast collection to be problematized, including, in the school environment. That said, we opted to carry out a participatory field research, which we used as tools of immersion in the investigated reality, observation, open interview and the construction of field diaries. Altogether it was 2 months of immersion in the field, in this case, part of the banks of the Tocantins River, between October and November 2020, for 3 times a week, on average 4 hours a day, in which fishermen and riverside dwellers were interviewed, who made it possible to understand the relevance of leisure fishing as a way of “escaping” from everyday chores, representing a moment of rest and recreation among peers. Thus, through the qualitative analysis of the field records, an intense relationship between the river was also perceived as a work space, but also for the promotion of playfulness and social gatherings that are indispensable for the community. Furthermore, the close relationship between riverside dwellers and the environment, brings to the fore the need to deepen the dialogue between body and nature, which is very expensive for Physical Education.